2012
DOI: 10.5194/bg-9-179-2012
|View full text |Cite
|
Sign up to set email alerts
|

Mapping tropical forest biomass with radar and spaceborne LiDAR in Lopé National Park, Gabon: overcoming problems of high biomass and persistent cloud

Abstract: Abstract. Spatially-explicit maps of aboveground biomass are essential for calculating the losses and gains in forest carbon at a regional to national level. The production of such maps across wide areas will become increasingly necessary as international efforts to protect primary forests, such as the REDD+ (Reducing Emissions from Deforestation and forest Degradation) mechanism, come into effect, alongside their use for management and research more generally. However, mapping biomass over high-biomass tropic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(138 citation statements)
references
References 33 publications
4
128
0
6
Order By: Relevance
“…This saturation level depends on the frequency, the polarization mode, incidence angle, the type of forest, foliage structure, and moisture conditions. As a result, a wide range of sensitivities has been reported, but rarely does the sensitivity exceed 100 Mg ha −1 for L-band polarimetric algorithms (Kasischke et al, 1997;Mitchard et al, 2012). The Phased Array type L-band Synthetic Aperture Radar (PALSAR) instrument on Advanced Land Observing Satellite (ALOS) builds on the Japanese Earth Resources Satellite (JERS-1) L-band Synthetic Aperture Radar (SAR) technology, provided the first systematic global observations for generating forest change and derived biomass maps, but failed in 2011.…”
Section: Biomassmentioning
confidence: 99%
“…This saturation level depends on the frequency, the polarization mode, incidence angle, the type of forest, foliage structure, and moisture conditions. As a result, a wide range of sensitivities has been reported, but rarely does the sensitivity exceed 100 Mg ha −1 for L-band polarimetric algorithms (Kasischke et al, 1997;Mitchard et al, 2012). The Phased Array type L-band Synthetic Aperture Radar (PALSAR) instrument on Advanced Land Observing Satellite (ALOS) builds on the Japanese Earth Resources Satellite (JERS-1) L-band Synthetic Aperture Radar (SAR) technology, provided the first systematic global observations for generating forest change and derived biomass maps, but failed in 2011.…”
Section: Biomassmentioning
confidence: 99%
“…Other vegetation data sets that can capture vegetation dynamics are for example the observations based on long-wavelength radar backscatter (Joshi et al, 2015), where deforestation, forest degradation and the follow-up vegetation cover could be captured, and those based on observations from the SeaWinds Ku-band scatterometer (Frolking et al, 2012), which have been shown to capture gross forest loss in the Tropics. Also lidar data can be used to estimate forest biomass, and can thus capture vegetation dynamics (Mitchard et al, 2012). Data availability for radar and lidar data sets is usually from 1998 onwards.…”
Section: J E Van Marle Et Al: Annual South American Forest Lossmentioning
confidence: 99%
“…More accurate measures of change are required, including quantitative measures of above ground biomass and stem density, which will allow preand post-treatment comparisons. Several studies have used large-scale methods to establish landscape level biomass: measures from forest plots in Lopé have already been used to quantify satellite imagery for estimating carbon stocks at a landscape level (Mitchard et al, 2011), and this approach could be extended to improve resolution for mapping above ground biomass…”
Section: Extent Of Fire Managementmentioning
confidence: 99%